Chlorhexidine whole-body washing of patients reduces methicillin-resistant Staphylococcus aureus and has a direct effect on the distribution of the ST5-MRSA-II (New York/Japan) clone - Velázquez Meza, Maria Elena; Mendoza Olazarán, Soraya Sarahí; Echániz Aviles, Gabriela; Camacho Ortiz, Adrián; Martínez Reséndez, Michel Fernando; Valero Moreno, Vanessa; Garza González, Elvira (2017)
Abstract Purpose. Methicillin-resistant Staphylococcus aureus (MRSA) colonizes the skin of hospitalized patients and is associated with high morbidity and mortality. To prevent colonization and infection by S. aureus, better disinfection practices are required. Therefore, we evaluated the effect of chlorhexidine whole-body washing on hospital-acquired S. aureus infections among intensive care unit (ICU) patients in a tertiary hospital in Mexico. Methodology. The study was conducted over 18 months to evaluate the effect of 2% chlorhexidine gluconate (CXG) wholebody washing of ICU adult patients on chlorhexidine and antibiotic resistance, biofilm production and clonal distribution of S. aureus in a tertiary care hospital. Minimum inhibitory concentrations for CXG, antibiotic susceptibility and biofilm production by S. aureus isolates were determined. Pulsed-field gel electrophoresis, multilocus sequence typing (MLST) and PCR for Panton–Valentine leucocidin (PVL) were used for molecular typing of MRSA isolates. Results/Keyfindings. We included 158 isolates. A reduction in antibiotic resistance in the study period was observed for clindamycin, levofloxacin, norfloxacin, oxacillin and trimethoprim/sulfamethoxazole. None of the isolates showed reduced susceptibility to CXG. Most of the isolates were non-biofilm producers (147/158). The most commonly identified clone was a descendant of the ST5-MRSA-II (New York/Japan) clone. This clone decreased during the intervention period and reappeared markedly in the post-intervention period. During the post-intervention period, two isolates were related with the clone ST8-MRSA-IV (also known as USA300). Conclusion. Our findings suggest that the CXG bathing favored the reduction of healthcare-associated MRSA isolates and a temporary reduction of the predominant ST5-MRSA-II (New York/Japan) clone.